Assistência pré-natal durante a pandemia da covid-19: o caso de Sobral - Sousa, Conceição de Maria Farias (2024)
Covid-19 is a disease caused by the coronavirus SARS-CoV-2 and has presented a greater risk of severity in patients with chronic diseases, such as heart disease, high blood pressure, diabetes, among others. The Brazilian Ministry of Health expanded this group at high risk of severity, including pregnant women, postpartum women and women after abortion, due to immunity and low tolerance to hypoxia (decrease in oxygen). The objective is to analyze the care strategies used by professional nurses in Sobral in prenatal consultations during the Covid-19 pandemic. The research scenario will take place in the municipality of Sobral, in the Family Health Strategy, in the municipality. The study participants were Primary Care nurses with the inclusion criteria being professionals working in care with at least six months of professional experience and working in the service during the COVID-19 Pandemic. As for the methodology, it will be exploratory research, with a qualitative approach, of the case study type. The case study aims to provide a certain experience of reality, based on discussion, analysis and the search for a solution to a given problem extracted from real life. In fact, it is a methodological strategy of wide use, when one intends to answer the questions 'how' and 'why' certain situations or phenomena that occur, especially when there are few possibilities of interference or control over events. studied. The data were analyzed using Bardin's content analysis technique, which consists of three phases: pre-analysis; exploration of the data obtained; and treatment of obtained results and interpretation. In the initial phase, pre-analysis, the material is organized, composing the research corpus. Documents are chosen, hypotheses are formulated and indicators are developed that guide the final interpretation. The ethical principles that govern research involving human beings will be respected. This project was initially submitted to the Scientific Committee of the Health Secretariat of Sobral (SICC) with a positive opinion of protocol acceptance, No. 0040/2023, subsequently, to the CEP, through the Brasil platform. The research respected all terms of Resolution 466/2012. The results were analyzed using the approach described above, where the following categories emerged: The analytical category (1) Adaptive prenatal care strategies in times of pandemic, was divided into an analysis subcategory: (1.1) Modified care procedures. The category (2) Nurses' perspectives: effectiveness and challenges in prenatal care strategies is divided into three subcategories: (2.1) Adaptation of care protocols, (2.2) Psychosocial and emotional challenges; (2.3) Continuing education of professionals. The category (3) Strategies to ensure effectiveness in prenatal care was divided into two subcategories: (3.1) Care and safety measures; (3.2) Reorganization of work processes and interprofessional collaboration. Thus, due to what was mentioned, it is possible to observe that health services and professionals were able to make adaptations during this critical situation involving the COVID-19 pandemic without ceasing to provide longitudinal assistance to women in prenatal care.